Intravenous thrombolysis in the emergency department for the treatment of acute ischaemic stroke. Issue 7 (23rd June 2008) - Semplicini, A; Benetton, V; Macchini, L; Realdi, A; Manara, R; Carollo, C; Parotto, E; Mascagna, V; Leoni, M; Calò, L A; Pessina, A C; Tosato, F
Abstract : Background and aims: Thrombolytic therapy with intravenous recombinant tissue plasminogen activator (rt-PA) improves outcome in patients with ischaemic stroke treated within 3 h of symptom onset, but its extended implementation is limited. A pilot study was designed to verify whether evaluation of patients with acute ischaemic stroke and their treatment with intravenous rt-PA in the emergency department (ED), followed by transportation to a semi-intensive stroke care unit, offers a safe and effective organisational solution to provide intravenous thrombolysis to acute stroke patients when a stroke unit (SU) is not available. Methods: After checking for inclusion and exclusion criteria, ED doctors contacted the stroke team with a single page, located family members and urgently obtained computed tomography scan and laboratory tests. A stroke team investigator clinically assessed the patient, obtained written informed consent and supervised intravenous rt-PA in the ED. After treatment, the patient was transferred to the SU for rehabilitation and treatment of complications, under supervision of the same stroke team investigator. Results: 52 patients were treated with intravenous rt-PA within 3 h of symptom onset. 20 patients (38%) improved neurologically after 24 h, the number increased to 30 (58%) after one week. At 3 months 22 patients had a favourable outcome (43%). The 3-month mortality rate was 12%. Symptomatic cerebral haemorrhage was observed in two patients (4%). Conclusions: Intravenous rt-PA administration in the ED is an effective organisational solution for acute ischaemic stroke when an SU is not established.